Survey of Candidate Single-Nucleotide Polymorphisms in SLC11A1, TLR4, NOD2, PGLYRP1, and IFNγ in Ankole Longhorn Cattle in Central Region of Uganda to Determine Their Role in Mycobacterium avium Subspecies paratuberculosis Infection Outcome - Okuni, Julius Boniface; Afayoa, Mathias; Ojok, Lonzy (Frontiers in Veterinary Science, 2021)
Mycobacterium avium subspecies paratuberculosis (MAP) is the cause of Johne’s disease (JD) in a wide range of domestic and wild ruminants. Single nucleotide polymorphisms (SNPs) in several genes including Solute like carrier molecules 11A1 (SLC11A1), Interferon gamma (IFNγ), Toll like receptor four (TLR4), Nucleotide-binding Oligomerization Domain 2 gene (NOD2) and Bovine Peptidoglycan recognition protein1 (PGLYRP1) have been implicated in influencing the infection outcome of MAP in cattle. We have carried out a survey in a population of Ankole cattle from three districts in the central region of Uganda including Isingiro, Lyantonde and Rakai, to determine the role played by several SNPs on the above genes in the infection outcome of local cattle in Uganda. Nine hundred fifty-five heads of cattle obtained from 95 herds were tested using ELISA. Thirty-five ELISA positive cattle and 35 negative herd mates from a total of 955 cattle tested for MAP were genotyped using iPLEX MassARRAY genotyping systems to detect the presence of a total of 13 SNPS in five different genes (SLC11A1, IFNγ, TLR4, NOD2 and PGLYRP1). The cow-level prevalence of MAP infection in Ankole Longhorn cattle in the three districts was 3.98% (35/955), while the herd-level prevalence was 27.9% and within herd-prevalence was 12±1.5% (95% C.I. = 9.1 – 14.8%). The genotypes and allele frequencies of the MAP positive cattle were compared with those of their ELISA negative herd mates to determine the significance of the polymorphisms. The results showed that SNPs rs109915208, rs110514940, rs110905610 on SLC11A1; c.480G>A, c.625C>A on PGLYRP1 and c.2021C>T on TLR4 were monomorphic in both seropositive and sero-negative cattle and therefore had no influence in the infection outcome. The remaining SNPs studied in the five genes (SLC11A1: rs109614179; TLR4: rs29017188 (c.226G>C), c.2021C>T; NOD2: rs110536091, rs111009394; PGLYRP1: c.102G>C, c.480G>A, c.625C>A; IFNγ: rs110853455) were polymorphic but their allele and genotype frequencies did not show any significant difference between the seropositive and seronegative cattle. No significant difference was observed for any haplotype at the gene level